Frontiers in electronics selected papers from the Workshop on Frontiers in Electronics 2011 (WOFE-11), San Juan, Puerto-Rico, 18-21 December 2011 - Cristoloveanu, Sorin; Shur, Michael S. (Selected topics in electronics and systems, 2013)
Frontiers in Electronics includes the best papers of WOFE-11 invited by the Editors and down selected after the peer review process. This book is conceived to make available in the international arena extended versions of selected, high impact talks. The papers are divided into four sections: advanced terahertz and photonics devices; silicon and germanium on insulator and advanced CMOS and MOSHFETs; nanomaterials and nanodevices; wide band gap technology for high power and UV photonics.